Analysis of Factors Affecting Public Awareness and Payment of Land and Building Tax in Jember Regency - Farida Umi Choiriyah; Miftakhul Jannah; Siti Nur Azizatul Luthfiyah; Ahmad Zubadul Afiq; Achmad Fawaid; Salman Alfarizy (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2026)
This Study examines the phenomenon of public awarness regarding tax payments for the sake of the common good (maslaha) in Jember Regency, an area administratively comprising 31 districts, 22 urban villages, and 226 rural villages. A qualitative phenomenological method was employed, utilizing primary data gathered through surveys and interviews with village and urban village officials. Secondary data werw obtained from statistics Indonesia (BPS) reports, books, and previous research journals. Informants were selected representatively from the 31 disctrics, covering 28 villages or urban villages distributed across five regions of Jember, purposive sampling was used to select these interviewees. Data analysis and validation techniques included prolonged engagement, triangulation, and member checking. The results reveal a disparity in tax payment awareness between urban and rural areas in Jember. Urban residents demonstrate higher compliance, supported by better education levels, economic conditions, and a greater understanding of the role of taxes in driving development. Conversely, awareness in rural areas varies, some residents do not pay taxes regularly, often waiting for collections officers to visit. However, one area ini South Jember stands out, despite being a rural setting, the community’s Land and Building Tax payment rate is notably high (60-80%). This is attributed to the local government’s strategic collection approach, which ties tax settlement to the processing of administrative documents at the village level. Delays in tax payments in Jember generally stemnot from economic inability, but from a lack of awareness, understanding, and information regarding tax obligations and payment schedules. Given that tax payment align with the concept of maslaha, as tax revenue returns to the community through infrastructure improvements, public facilities, education, healthcare, and government subsidies, it is essential to enhance public outreach and education regarding tax payments for the benefit of the people of Jember